Dermatophyte surveillance in cats in three animal shelters in Ontario, Canada. Issue 1 (January 2017) - Mozes, Rachael; Pearl, David L; Rousseau, Joyce; Niel, Lee; Weese, J Scott
Objectives: The aim of the study was to determine the prevalence of dermatophyte shedding in cats admitted to three Ontario animal shelters from February to May 2013. Methods: Four hundred cats were sampled within 48 h of admission, using a standard toothbrush sampling technique. Dermatophyte culture was performed. Results: Dermatophytes were not identified in any of the 400 cats (0–0.9% one-sided exact 97.5% confidence interval). Conclusions and relevance: These results imply that dermatophyte shedding is rare in cats admitted to Ontario animal shelters. Consequently, identification of infected animals, particularly multiple animals, represents an unusual occurrence that may justify prompt and intensive control measures.